Zinc-based catalyst for gas-solid phase acetylene hydration reaction and preparation method thereof
By using the doping technology of carbon shell and sulfur atoms of the metal organic framework ZIF-8 in the zinc-based catalyst, the problems of poor stability and carbon deposit formation in the acetylene hydration reaction are solved, and efficient, stable and environmentally friendly catalytic effects are achieved.
Patent Information
- Application Number
- CN202411721961.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The existing catalysts have poor stability, loss of active components and carbon deposits in the acetylene hydration reaction, which affects the efficiency and life of the catalyst.
Using a zinc-based catalyst, a carbon shell is formed during the derivation of the precursor of the metal organic framework ZIF-8, and combined with the doping of sulfur atoms, the Zn-NSC-T catalyst is formed. The catalyst significantly improves stability and activity through doping of sulfur atoms, and inhibits the formation of carbon deposits.
It significantly improves the stability and activity of the catalyst, improves the conversion rate of acetylene and the selectivity of acetaldehyde, extends the service life of the catalyst, and reduces the formation of carbon deposits.
Smart Images

Figure CN119549179A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst preparation, in particular to a zinc-based catalyst for gas-solid phase acetylene hydration reaction and a preparation method thereof. Background Art
[0002] The preparation of acetaldehyde by acetylene hydration reaction is an important unit for producing acetaldehyde downstream products in my country. Acetaldehyde can be used to produce acetic acid, pentaerythritol, ethyl acetate, pyridine compounds and crotonaldehyde, etc., and has a wide range of applications in the fields of pesticides, medicines, feed and food additives. There are two ways to produce acetaldehyde: acetylene hydration and ethylene oxidation, but ethylene mainly comes from the cracking of petroleum. According to the characteristics of my country's energy structure, the development of chemical products based on coal is an inevitable trend. Therefore, it is particularly important to develop a simple and efficient catalyst for producing acetaldehyde.
[0003] At present, acetaldehyde is mainly produced by hydration reaction of acetylene with catalysts. Among them, the acetylene conversion rate and acetaldehyde selectivity of the catalyst are crucial. In the early stage of synthesizing acetaldehyde by gas-solid phase acetylene hydration method, the catalyst with zeolite as carrier was mainly used.
[0004] However, this type of catalyst still has many shortcomings. Later, more and more researchers began to study from the aspects of carrier modification, transition metal doping, ligand modification, catalytic mechanism, etc. Although certain research results have been achieved, the poor stability of the catalyst, loss of active components and carbon deposition are still key issues that need to be studied. Therefore, it does not meet the existing needs. In this regard, we propose a zinc-based catalyst for gas-solid phase acetylene hydration reaction and its preparation method. Summary of the invention
[0005] The purpose of the present invention is to provide a zinc-based catalyst for gas-solid phase acetylene hydration reaction and a preparation method thereof, so as to solve the problem that the catalyst proposed in the above background technology participates in the acetylene hydration reaction to produce acetaldehyde. There are many shortcomings in this type of catalyst. Later, more and more researchers began to study from the aspects of carrier modification, transition metal doping, ligand modification, catalytic mechanism, etc. Although certain research results have been achieved, the poor stability of the catalyst, loss of active components and carbon deposition are still problems that need to be studied.
[0006] To achieve the above object, the present invention provides the following technical solution: a zinc-based catalyst for gas-solid phase acetylene hydration reaction, the zinc-based catalyst comprising a zinc source, an organic ligand, a deprotonating agent, and a sulfur source dopant;
[0007] The zinc source is zinc chloride;
[0008] The organic ligand is 2-methylimidazole;
[0009] The deprotonating agent is triethylamine;
[0010] The sulfur source dopant is sodium diethyldithiocarbamate trihydrate.
[0011] A method for preparing a zinc-based catalyst for gas-solid phase acetylene hydration reaction comprises the following steps:
[0012] Step 1: Prepare two clean 500ml beakers and mark them as No. 1 and No. 2, add 200ml of deionized water and magnet respectively, turn on the magnetic stirrer, adjust the stirrer constant temperature system to 20-40℃, and the stirring rate to 500rpm;
[0013] Step 2: While maintaining the temperature at 20-40°C and the stirring rate at 500 rpm, add 1.35 g of zinc chloride to beaker No. 1 and continue stirring for 10 minutes to form a uniform solution;
[0014] Step 3: While maintaining the temperature at 20-40°C and the stirring rate at 500 rpm, add 6.5 g of 2-methylimidazole to beaker No. 2 and stir for 10 min to completely dissolve the 2-methylimidazole, then add 1 g of sodium diethyldithiocarbamate trihydrate to beaker No. 2 and continue stirring for 10 min to form a uniformly mixed solution;
[0015] Step 4: Use a clean 25 ml measuring cylinder to measure 15 ml of triethylamine and add it to beaker No. 2. Continue stirring for 10 minutes to form a uniform solution.
[0016] Step 5: While maintaining the temperature at 20-40°C and the stirring rate of the stirrer in beaker No. 2 at 600 rpm, the solution in beaker No. 1 was quickly poured into beaker No. 2 and stirred for 2 hours to form sulfur-modified ZIF-8, which was labeled as S-ZIF-8;
[0017] Step 6: Use a suction filtration funnel with an inner diameter of 8 cm to filter the product in beaker No. 2, and use 500 ml of deionized water to wash the product during the filtration process;
[0018] Step 7: Move the funnel containing the washed product into a constant temperature drying oven with a perforated tin foil and dry it at 80°C for 10 hours. After cooling, grind the product and put it into a clean ceramic ark. In an argon atmosphere, increase the temperature to T at a rate of 5°C / min and keep it warm for 4 hours. After cooling, obtain the catalyst, which is marked as Zn-NSC-T. Perform a catalytic activity test on the catalyst and store it in a sample bag for later use.
[0019] Preferably, the temperature T includes 500°C, 600°C, 700°C and 800°C.
[0020] Preferably, the catalyst activity test comprises the following steps:
[0021] S1: Purge the catalyst with N2 to exhaust the impurity gas in the reaction device;
[0022] S2: Acetylene hydration reaction is carried out in a continuous fixed-bed flow microreactor under normal pressure. The inner diameter of the continuous fixed-bed flow microreactor under normal pressure is 10 mm. About 2 ml of catalyst sample is placed in the tubular reactor, and the tubular reactor is placed in the middle of the reactor furnace;
[0023] S3: Heating is performed, and the temperature of the condensation circulation pump is set to about -2°C. When the reaction temperature reaches temperature S1 and the displayed temperature of the reaction water reaches temperature S2, the catalyst in the fixed bed reactor is activated by water vapor (0.012 g min -1 ), the activation time is thirty minutes;
[0024] S4: Turn off the N2 switch, wait until the nitrogen flow meter shows zero, then turn on C2H2, according to GHSV (C2H2) = 90h -1 and n(H2O) / n(C2H2)=4, injecting acetylene and water vapor into the reactor;
[0025] S5: The product content was checked every hour by manual injection of gas chromatography.
[0026] Preferably, the main product of the acetylene hydration reaction is acetaldehyde, and the by-products include acetone and crotonaldehyde, as well as acetylene that does not participate in the reaction.
[0027] Preferably, the calculation formula for the conversion rate of acetylene and the selectivity of acetaldehyde is:
[0028]
[0029]
[0030] in, represents the volume fraction of C2H2 in the raw material, represents the residual C2H2 volume fraction in the product, Represents the volume fraction of CH3CHO in the reaction product.
[0031] Preferably, the temperature S1 is 260°C.
[0032] Preferably, the temperature S2 is 170°C.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. The present invention forms a carbon shell on the surface of the carbon material derived from the metal organic framework ZIF-8 as a precursor, which effectively inhibits the loss of zinc and improves the stability of the catalyst to a certain extent. The carbon material derived from the metal organic framework is used, the active metal is evenly dispersed, and the doping of sulfur atoms inhibits the formation of carbon deposits to a certain extent, thereby improving the stability of the catalyst;
[0035] 2. The present invention makes the entire catalytic system more stable and has higher catalytic activity by doping with sulfur atoms. The conversion rate of acetylene and the selectivity of acetaldehyde are significantly improved. Acetylene activation is the rate-controlling step of the reaction. The doping of sulfur atoms significantly reduces the energy barrier of acetylene activation during the acetylene hydration reaction, making the reaction easier to proceed;
[0036] 3. The Zn-NSC catalyst prepared by the present invention uses ZIF-8 with high porosity, adjustable crystal structure and good thermal stability as a precursor, and sodium diethyldithiocarbamate trihydrate as a heteroatom dopant, and has the characteristics of low price and high yield. Therefore, the present invention is a new synthesis method that is efficient, stable, environmentally friendly and economical. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 A schematic diagram of the performance of the catalyst prepared in the present invention in catalyzing hydration of acetylene;
[0038] Figure 2 This is a schematic diagram of XRD characterization of the catalyst prepared in the present invention;
[0039] Figure 3 Schematic diagram of TG characterization of the Zn-NSC-600 catalyst prepared in the present invention;
[0040] Figure 4 This is a schematic diagram of XPS characterization of the Zn-NSC-600 catalyst prepared in the present invention;
[0041] Figure 5 Schematic diagram of XAFS characterization of the Zn-NSC-600 catalyst prepared in the present invention. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0043] See also Figures 1 to 5 , an embodiment provided by the present invention: a zinc-based catalyst for gas-solid phase acetylene hydration reaction, the zinc-based catalyst comprising a zinc source, an organic ligand, a deprotonating agent, and a sulfur source dopant;
[0044] The zinc source is zinc chloride;
[0045] The organic ligand is 2-methylimidazole;
[0046] The deprotonating agent is triethylamine;
[0047] The sulfur source dopant is sodium diethyldithiocarbamate trihydrate.
[0048] A method for preparing a zinc-based catalyst for gas-solid phase acetylene hydration reaction comprises the following steps:
[0049] Step 1: Prepare two clean 500ml beakers and mark them as No. 1 and No. 2, add 200ml of deionized water and magnet respectively, turn on the magnetic stirrer, adjust the stirrer constant temperature system to 20-40℃, and the stirring rate to 500rpm;
[0050] Step 2: While maintaining the temperature at 20-40°C and the stirring rate at 500 rpm, add 1.35 g of zinc chloride to beaker No. 1 and continue stirring for 10 minutes to form a uniform solution;
[0051] Step 3: While maintaining the temperature at 20-40°C and the stirring rate at 500 rpm, add 6.5 g of 2-methylimidazole to beaker No. 2 and stir for 10 min to completely dissolve the 2-methylimidazole, then add 1 g of sodium diethyldithiocarbamate trihydrate to beaker No. 2 and continue stirring for 10 min to form a uniformly mixed solution;
[0052] Step 4: Use a clean 25 ml measuring cylinder to measure 15 ml of triethylamine and add it to beaker No. 2. Continue stirring for 10 minutes to form a uniform solution.
[0053] Step 5: While maintaining the temperature at 20-40°C and the stirring rate of the stirrer in beaker No. 2 at 600 rpm, the solution in beaker No. 1 was quickly poured into beaker No. 2 and stirred for 2 hours to form sulfur-modified ZIF-8, which was labeled as S-ZIF-8;
[0054] Step 6: Use a suction filtration funnel with an inner diameter of 8 cm to filter the product in beaker No. 2, and use 500 ml of deionized water to wash the product during the filtration process;
[0055] Step 7: Move the funnel containing the washed product into a constant temperature drying oven with a perforated tin foil and dry it at 80°C for 10 hours. After cooling, grind the product and put it into a clean ceramic ark. Under an argon atmosphere, heat it to temperature T at a rate of 5°C / min and keep it warm for 4 hours. The temperature T includes 500°C, 600°C, 700°C and 800°C. After cooling, the catalyst is obtained. The catalyst is marked as Zn-NSC-T. The catalyst activity is tested and stored in a sample bag for later use.
[0056] The T in Zn-NSC-T can be 500, 600, 700 and 800, and the numbers correspond to the temperature T of 500℃, 600℃, 700℃ and 800℃, as follows:
[0057] Synthesis of Zn-NSC-500 catalyst: The prepared S-ZIF-8 precursor was transferred to a ceramic ark, heated to 500°C at a heating rate of 5°C / min under an argon atmosphere, and then kept warm for 4h. After cooling, the sample was obtained and recorded as Zn-NSC-500. The obtained material was used directly without further processing;
[0058] Synthesis of Zn-NSC-600 catalyst: The prepared S-ZIF-8 precursor was transferred to a ceramic ark, heated to 600°C at a heating rate of 5°C / min under an argon atmosphere, and then kept warm for 4h. After cooling, the sample was obtained and recorded as Zn-NSC-600. The obtained material was used directly without further processing;
[0059] Synthesis of Zn-NSC-700 catalyst: The prepared S-ZIF-8 precursor was transferred to a ceramic ark, heated to 700°C at a heating rate of 5°C / min under an argon atmosphere, and then kept warm for 4h. After cooling, the sample was obtained and recorded as Zn-NSC-700. The obtained material was used directly without further processing;
[0060] Synthesis of Zn-NSC-800 catalyst: The prepared S-ZIF-8 precursor was transferred to a ceramic ark, heated to 800°C at a heating rate of 5°C / min under an argon atmosphere, and then kept warm for 4h. After cooling, the sample was obtained and recorded as Zn-NSC-800. The obtained material was used directly without further processing.
[0061] The catalyst activity test includes the following steps:
[0062] S1: Purge the catalyst with N2 to exhaust the impurity gas in the reaction device;
[0063] S2: Acetylene hydration reaction is carried out in a continuous fixed-bed flow microreactor under normal pressure. The inner diameter of the continuous fixed-bed flow microreactor under normal pressure is 10 mm. About 2 ml of catalyst sample is placed in the tubular reactor, and the tubular reactor is placed in the middle of the reactor furnace;
[0064] S3: Heating is performed, and the temperature of the condensation circulation pump is set to about -2°C. When the reaction temperature reaches 260°C, the reaction pressure is normal pressure, and the acetylene space velocity is 90h -1 When the displayed temperature of the reaction water reaches 170°C, the catalyst in the fixed bed reactor is activated by water vapor (0.012 g min -1 ), the activation time is thirty minutes;
[0065] S4: Turn off the N2 switch, wait until the nitrogen flow meter shows zero, then turn on C2H2, according to GHSV (C2H2) = 90h -1 and n(H2O) / n(C2H2)=4, injecting acetylene and water vapor into the reactor;
[0066] S5: Manual sampling by gas chromatography is performed every hour to detect the content of the product and analyze its composition.
[0067] The products obtained from the acetylene hydration reaction were quantitatively analyzed using the calibration area normalization method. The conversion rate of acetylene (X) and the selectivity of acetaldehyde (S) are used to evaluate the performance of zinc-based catalysts in the acetylene hydration reaction. The main product of the acetylene hydration reaction is acetaldehyde, and the by-products are acetone and crotonaldehyde, as well as acetylene that does not participate in the reaction. The conversion rate of acetylene and the selectivity of acetaldehyde are calculated as follows:
[0068]
[0069] in, represents the volume fraction of C2H2 in the raw material, represents the residual C2H2 volume fraction in the product, It indicates the volume fraction of CH3CHO in the product after the reaction. The level of X is used to measure the amount of reactants in the product. The higher the C2H2 conversion rate, the greater the consumption of C2H2. S is a measure of the amount of acetaldehyde, the target product. The higher the selectivity of acetaldehyde, the more acetaldehyde is generated in the reaction.
[0070] Acetylene conversion and acetaldehyde selectivity of Zn-NSC-T catalysts prepared at different calcination temperatures, as shown in the instruction manual Figure 1As shown in the figure, the catalytic performance test results show that the Zn-NSC-T catalyst has the best performance when the calcination temperature is 600°C. The optimal Zn-NSC-600 catalyst still has a selectivity of about 74% for acetaldehyde after 16 hours of reaction, indicating that the nitrogen and sulfur co-doped carbon-zinc-based catalyst prepared at a suitable calcination temperature can better overcome the problem of high initial selectivity for acetaldehyde and then rapid decline in Zn-based catalysts.
[0071] The catalysts prepared in the examples of the present invention were subjected to various characterization tests.
[0072] The loss of active components is an important factor in catalyst deactivation. In order to study the anti-loss performance of the catalyst, the catalyst of Zn-NSC-600 reaction for 16 hours and the fresh catalyst were tested by ICP-OES. The results are listed in Table 1. Table 1 shows that the loss rate of Zn in the Zn-NSC-600 catalyst is only. The results show that the Zn-NSC-600 catalyst has good anti-loss performance and exhibits excellent catalytic performance in acetylene hydration.
[0073] Table 1
[0074]
[0075] The crystal structure of the catalyst was analyzed using X-ray diffraction technology. The results are shown in the attached manual. Figure 2 As shown, no diffraction peak of Zn-containing substances was detected in the catalyst before the reaction, indicating that the Zn active component has good dispersibility.
[0076] Carbon deposition is an important factor in catalyst deactivation. In order to study the anti-carbon deposition performance of the catalyst, the catalyst after 16 hours of reaction of Zn-NSC-600 and the fresh catalyst were subjected to TG characterization analysis. The results are shown in the attached manual. Figure 3 As shown, the carbon deposition was calculated by estimating the weight difference between the new catalyst and the old catalyst in the same temperature range. The weight loss difference of the catalyst at 400℃-900℃ can be regarded as carbon deposition. The carbon deposition amount of Zn-NSC-600 catalyst was only. The results showed that Zn-NSC-600 catalyst had good thermal stability and anti-carbon deposition performance, and therefore exhibited good catalytic performance in acetylene hydration reaction.
[0077] The surface electronic structure of the Zn-NSC-600 catalyst was analyzed by X-ray photoelectron spectroscopy (XPS). Figure 4 As shown in the figure, the XPS full spectrum of the Zn-NSC-600 catalyst confirms the presence of Zn, N, S and C atoms. There are two characteristic peaks S2p in the X-ray photoelectron spectrum of S2p. 3 / 2 (161.56 eV) and S2p 1 / 2(163.99eV), indicating the presence of CSC (N). No Zn-S signal was observed in the S2p spectrum, indicating that there is no direct coordination relationship between the S species and the Zn species. From the C1s spectrum of the Zn-NSC catalyst, it can be seen that after S doping, the peak of the CS bond (285.99eV) was observed in the C1s spectrum of the Zn-NSC, indicating that the S atoms were doped in the carbon support in the form of CS bonds.
[0078] The catalyst was characterized by X-ray absorption fine structure spectroscopy (XAFS) and the local coordination structure of Zn-NSC-600 catalyst was analyzed. Figure 5 As shown. The Zn K-edge (XANES) spectrum results show that the absorption edge of the Zn-NSC-600 catalyst is located between the absorption edges of Zn foil and ZnO, indicating that the valence state of the Zn substance in the Zn-NSC-600 catalyst is between 0 and +2. The extended X-ray absorption fine structure (EXAFS) spectrum results show that Zn-NSC-600 has only one main peak at 1.5μm, which is similar to zinc phthalocyanine and belongs to the Zn-N path. No signals of the Zn-Zn path (about 2.3μm) and the Zn-S path (about 1.8μm) were observed, indicating that in the atomic structure of Zn-NSC-600, Zn is only coordinated with N, not with sulfur. The Zn-NSC-600, Zn foil, and ZnPc were fitted to further understand the structural parameters of the metal atoms in the materials. The EXAFS structural parameters are listed in Table 2. Table 2 is shown below. The results show that the Zn atom is coordinated with three N atoms, and the Zn-N bond length is
[0079] Table 2
[0080]
[0081]
[0082] (aCN: coordinationnumber; b R:distancebetweenabsorberandbackscatteratoms; c σ 2 :Debye-Wallerfactortoaccountforboththermalandstructuraldisorders; d ΔE0:innerpotentialcorrection; Rfactorindicatesthegoodnessofthefit.S0 2wasfixedto0.87.AreasonablerangeofEXAFSfittingparameters:0.600 <S0 2 <1.000; CN>0; |ΔE0|<15eV; Rfactor<0.02)
[0083] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A zinc-based catalyst for gas-solid phase acetylene hydration reaction, characterized in that: The zinc-based catalyst comprises a zinc source, an organic ligand, a deprotonating agent, and a sulfur source dopant; The zinc source is zinc chloride; The organic ligand is 2-methylimidazole; The deprotonating agent is triethylamine; The sulfur source dopant is sodium diethyldithiocarbamate trihydrate.
2. A method for preparing a zinc-based catalyst for gas-solid phase acetylene hydration reaction, characterized in that: The steps include: Step 1: Prepare two clean 500ml beakers and mark them as No. 1 and No. 2, add 200ml of deionized water and magnet respectively, turn on the magnetic stirrer, adjust the stirrer constant temperature system to 20-40℃, and the stirring rate to 500rpm; Step 2: While maintaining the temperature at 20-40°C and the stirring rate at 500 rpm, add 1.35 g of zinc chloride to beaker No. 1 and continue stirring for 10 minutes to form a uniform solution; Step 3: While maintaining the temperature at 20-40°C and the stirring rate at 500 rpm, add 6.5 g of 2-methylimidazole to beaker No. 2 and stir for 10 min to completely dissolve the 2-methylimidazole, then add 1 g of sodium diethyldithiocarbamate trihydrate to beaker No. 2 and continue stirring for 10 min to form a uniformly mixed solution; Step 4: Use a clean 25 ml measuring cylinder to measure 15 ml of triethylamine and add it to beaker No.
2. Continue stirring for 10 minutes to form a uniform solution. Step 5: While maintaining the temperature at 20-40°C and the stirring rate of the stirrer in beaker No. 2 at 600 rpm, the solution in beaker No. 1 was quickly poured into beaker No. 2 and stirred for 2 hours to form sulfur-modified ZIF-8, which was labeled as S-ZIF-8; Step 6: Use a suction filtration funnel with an inner diameter of 8 cm to filter the product in beaker No. 2, and use 500 ml of deionized water to wash the product during the filtration process; Step 7: Move the funnel containing the washed product into a constant temperature drying oven with a perforated tin foil and dry it at 80°C for 10 hours. After cooling, grind the product and put it into a clean ceramic ark. In an argon atmosphere, increase the temperature to T at a rate of 5°C / min and keep it warm for 4 hours. After cooling, obtain the catalyst, which is marked as Zn-NSC-T. Perform a catalytic activity test on the catalyst and store it in a sample bag for later use.
3. The method for preparing a zinc-based catalyst for gas-solid phase acetylene hydration reaction according to claim 2, characterized in that: The temperature T includes 500°C, 600°C, 700°C and 800°C.
4. The method for preparing a zinc-based catalyst for gas-solid phase acetylene hydration reaction according to claim 3, characterized in that: The catalyst activity test includes the following steps: S1: Purge the catalyst with N2 to exhaust the impurity gas in the reaction device; S2: Acetylene hydration reaction is carried out in a continuous fixed-bed flow microreactor under normal pressure. The inner diameter of the continuous fixed-bed flow microreactor under normal pressure is 10 mm. About 2 ml of catalyst sample is placed in the tubular reactor, and the tubular reactor is placed in the middle of the reactor furnace; S3: Heating is performed, and the temperature of the condensation circulation pump is set to about -2°C. When the reaction temperature reaches temperature S1 and the displayed temperature of the reaction water reaches temperature S2, the catalyst in the fixed bed reactor is activated by water vapor (0.012 g min -1 ), the activation time is thirty minutes; S4: Turn off the N2 switch, wait until the nitrogen flow meter shows zero, then turn on C2H2, according to GHSV (C2H2) = 90h -1 and n(H2O) / n(C2H2)=4, injecting acetylene and water vapor into the reactor; S5: The product content was checked every hour by manual injection of gas chromatography.
5. The method for preparing a zinc-based catalyst for gas-solid phase acetylene hydration reaction according to claim 4, characterized in that: The main product of the acetylene hydration reaction is acetaldehyde, and the by-products include acetone and crotonaldehyde, as well as acetylene that does not participate in the reaction.
6. The method for preparing a zinc-based catalyst for gas-solid phase acetylene hydration reaction according to claim 5, characterized in that: The calculation formula for the conversion rate of acetylene and the selectivity of acetaldehyde is: X C2H2 =[(φ A0 -f A ) / φ A0 ]×100%; S CH3CHO =[φ AA / (φ A0 -f A )]×100%; Among them, φ A0 Indicates the volume fraction of C2H2 in the raw material, φ A represents the residual C2H2 volume fraction in the product, φ AA Represents the volume fraction of CH3CHO in the reaction product.
7. The method for preparing a zinc-based catalyst for gas-solid phase acetylene hydration reaction according to claim 4, characterized in that: The temperature S1 is 260°C.
8. The method for preparing a zinc-based catalyst for gas-solid phase acetylene hydration reaction according to claim 4, characterized in that: The temperature S2 is 170°C.
Citation Information
Patent Citations
Catalyzing system for preparing acetaldehyde by acetylene liquid-phase hydratation and application thereof
CN108311174A
Efficient coupling method of anode oxidization hypochlorite production and cathode carbon dioxide reduction
CN109881213A
Sulfur-doped graphdiyne in-situ growth ZIF-67 material as well as preparation method and application thereof
CN115025786A
N, S co-doped carbon material loaded zinc monatomic and preparation method and application thereof
CN115845892A
Preparation method of metal monatomic catalyst and metal monatomic catalyst
CN117427657A